Coronary computed tomography angiography (CCTA) in patients with suspected stable coronary artery disease (CAD): diagnostic impact and clinical consequences in the German Cardiac CT Registry depending on stress test results - Barth, Sebastian; Hausleiter, Joerg; Moshage, Werner; Korosoglou, Grigorios; Leber, Alexander; Schmermund, Axel; Gohlke, Helmut; Bruder, Oliver; Dill, Thorsten; Schroeder, Stephen; Kerber, Sebastian; Hamm, Karsten; et al. (International Journal of Cardiovascular Imaging, 2019)
To evaluate diagnostic impact of clinical use of coronary computed tomography angiography (CCTA) in patients with suspected stable coronary artery disease (CAD) and its consequences in daily practice for patient management, depending on stress test results in daily practice. Between 2009 and 2014 of a total population of 1352 patients of the German Cardiac Computed Tomography (CT) Registry who had previously undergone stress tests, CCTA visualizations were carried out on the coronary arteries with suspected stable CAD. Patients were divided into three groups according to stress test results: Group 1 with inconclusive (n = 178, 13.2%), Group 2 with ischemia in stress test (n = 372, 27.5%) and Group 3 without ischemia in stress test (n = 802, 59.3%). The test of preference was the stress electrocardiogram (ECG), which was performed more frequently in patients without ischemia in stress test as compared to those with ischemia (96.3% vs. 93.0%, p = 0.015). The incidence of detected obstructive CAD was lower in patients with suggested ischemia in stress test as compared to patients with inconclusive results (14.1% vs. 21.1%, p = 0.037). There was no difference in the incidence of an obstructive CAD in patients with and without ischemia in stress test (14.1% vs. 15.8%, p = 0.440). CCTA is a reliable, non-invasive option for ruling-out obstructive CAD irrespective of the stress test result.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Coronary computed tomography angiography; Pre-test probability; Stable coronary artery disease; Stress test